The OPQ 32i (Occupational Personality Questionnaire 32 Version i) as a predictor of employee theft in a financial institution - Nobre, Michelle (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MA (Industrial Psychology))--University of Stellenbosch, 2005.